A comparison of the marginal and internal fit of CAD/CAM fabricated metal alloy fixed partial dentures/ Mohd Faiz Nasruddin ... [et al.] - Nasruddin, Mohd Faiz; Theocharospoulos, Antonios; Ray, Noel; Burke, Francis M (Faculty of Dentistry, 2016)
Fitting accuracy of dental prostheses is essential for clinical success. An ideal marginal and internal fit will minimize plaque accumulation, gingival irritation, cement dissolution and micro leakage as well as enhancing the mechanical behaviour of a fixed partial denture (FPD) (1). Unfortunately, there is disagreement about acceptable marginal and internal fit discrepancies of FPD's (2) from 75-200μm. The range of discrepancies stated (75-200µm) does not jeopardize the clinical performance of the restoration. However, McLean and von Fraunhofer (3) reported that marginal gaps of less than 120μm are clinically acceptable while gaps of less than 80μm are difficult to detect clinically.